1998
DOI: 10.1021/bi981765a
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Effector Domain of MARCKS and MARCKS-Related Protein with Lipid Membranes Revealed by Electric Potential Measurements

Abstract: We have investigated the binding of the effector domains of myristoylated alanine-rich C kinase substrate (MARCKS) and of MARCKS-related protein (MRP) to lipid model membranes. For membrane systems we used lipid monolayers on a Langmuir trough and black lipid membranes (BLM). The binding of the peptides was detected by monitoring changes in the boundary potential of the lipid membranes. The vibrating plate technique (VPT) and the method of inner field compensation (IFC) were used for the monolayer and for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…This is furthermore in line with the simultaneous timing and phoshorylation of MARCKS, an established PKC target also at the cell membrane. It is worth mentioning that phosphorylation of MARCKS by PKC leads to their detachment from the plasma membrane, which unmasks and increases the accessible lipid second messenger, PIP 2 , and is important for the activation of downstream signaling events [35][36][37]. Thus, our findings suggest that cPKC may play a more global role in TLR2-induced cellular processes and control phagocytosis, cytoskeletal changes and other signaling events.…”
Section: Discussionmentioning
confidence: 66%
“…This is furthermore in line with the simultaneous timing and phoshorylation of MARCKS, an established PKC target also at the cell membrane. It is worth mentioning that phosphorylation of MARCKS by PKC leads to their detachment from the plasma membrane, which unmasks and increases the accessible lipid second messenger, PIP 2 , and is important for the activation of downstream signaling events [35][36][37]. Thus, our findings suggest that cPKC may play a more global role in TLR2-induced cellular processes and control phagocytosis, cytoskeletal changes and other signaling events.…”
Section: Discussionmentioning
confidence: 66%
“…The partition coefficients obtained by fitting the data to Eq. [5] (straight lines) as well as the standard deviation and the number of experiments can be found in Table 1 0.8 (22,29). We found that this method does not significantly change the estimation of K p (not shown).…”
Section: Figmentioning
confidence: 77%
“…K p was finally determined by fitting the resulting values of f to Eq. [5]. Note that it was not necessary to correct the data for the exclusion volume of the beads (e.g., 6% of the total volume at a total lipid concentration of 1 mM).…”
Section: Determination Of Partition Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…This PD depends on many factors, such as the concentration of the electrolyte, its ability to penetrate the protein layer, and the distribution of fixed charges in this layer (35). Although the theory of the IFC method was developed to analyze the adsorption of small molecules, reliable results are obtained from the adsorption of large protein molecules as well (36)(37)(38). The simplest classic model of the relationship between the potential and surface charge density, which is proportional to the amount of protein molecules on the surface, is the equation of Gouy and Chapman (39,40),…”
Section: Purification Of M1 Proteinmentioning
confidence: 99%